KELAYAKAN EKONOMI ASBUTON PILOT PROJECT ASBUTON DI KALIMANTAN TENGAH - Yamin, R. Anwar (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2007)
Road development in Indonesia in average needs 1,2 million ton of asphalt. 600 thousand ton fromthat amount supplied by Pertamina and the rest has been imported from various countries. The volume of imported asphalt which nearby 50% of national need, of course, give a negative impact to Indonesia. Because of that, a continuity optimalization effort for using asbuton has been kept. Since asbuton invented, the technology of using asbuton keep evolutes from conventional asbuton. fine asbuton, micro asbuton, asbuton mastic. granulated asbuton and pure asbuton. The use of granulated asbuton have conducted on project scale in five provinces in Indonesia and concluded that technically asphaltic asbuton mixture could be produced and applicated in field and the mixture shown better performance compared to conventional asphaltic mixture. Not only the choice of asphaltic mixtures type is not depend solely on technical reason, but also economic reason. The aim of this study is to know the economy feasibility of using granulated asbuton in asphaltic mixture in Middle Borneo. This study concluded that the use of granulated asbuton as a pavement materials gave a positive effect on economic aspect, as it reduced the use of refinery asphalt and aggregate. In its optimum dozes, the price of AC-WC contained asbuton in type of B5/20 and B15/20 is economically feasible compared to AC-WC without asbuton with the same thickness when maximum ratio of asbuton price is 0.2 of refinery asphalt. And for Bl5/25 and B20/25 asbuton types, the maximum ratio is 0.25. For the same service life, asbuton type of B5/20 is economically feasible when its maximum price ratio to refinery asphalt is 0.5. And for Bl5/20, Bl5/25 and B20/25 type of asbuton its maximum ratio are 0.4.